Subjective quality of life and cardiovascular risk factors in a Croatian adult population - Benjak, Tomislav, liječnik (Array, 2009)
Summary: The objective of this study was to examine prevalence of cardiovascular (CV) risk factors and presence of cardiovascular diseases (CVD) in people with low subjective quality of life (SQoL) in comparison with group of people with normal SQoL. A total of 9070 participants, 2890 men and 6180 women completed a questionnaire. SQoL was assessed with single item question on satisfaction with life as a whole, and data on risk behaviors and diagnosed CVD were obtained through self-reports. Biomedical measures were administrated by public health nurse at participant’s home. Results have shown that people with low SQoL have significantly more CV risk factors, and have higher prevalence of obesity and physical inactivity, all irrespective to age group. The most pronounced difference in prevalence of CV risks was found in an age group 35 to 64 years of age where people with low SQoL have significantly higher prevalence of all measured risk behaviors, and physical conditions. Participants with low SQoL perceive their general health poorer, and experience negative and depressive feelings more frequently than those with normal SQoL, in all three age groups (p<0.001). Implications of the results have been discussed. Low SQoL was recognized as a psychological state that represents potential risk factor for the CV health. Prospective studies are needed to allow causal inferences to be drawn